Epigrafía medieval y epigrafía moderna en la provincia de Valladolid - Martínez Ortega, Ricardo (2006)
Se presenta la edición de una inscripción medieval latina y otra castellana de la colegiata de Santa María de Valladolid, así como el testimonio de un poema de San Eugenio trasladado a una inscripción de San Román de Hornija en el año 1858, a lo que se suman otros comentarios sobre el episemon y otras cuestiones.
«Medieval Epigraphy and Modern Epigraphy in the Province of Valladolid». This paper includes the edition of a medieval Latin inscription and a Castilian one from St. Mary’s collegiate church in Valladolid, and also the testimony of a poem by San Eugenio of Toledo transcribed to a inscription in San Román de Hornija in 1858, to which some comments on the episemon and other aspects are added.
Keywords: Epigrafía -- Valladolid